Correlation of the HPV genotype with the degree of dysplasia in patients with cervicouter cancer in the General Hospital Naval of high specialty - Morales, Oyuki A.; Araiza, Junior J.; Garay, María del R.; Barbabósa, Jorge A.; Gutiérrez, Marlene de la P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical-uterine cancer (CaCu) is the second leading cause of death in women worldwide and the first in developing countries. It has been correlated to human papillomavirus (HPV) genotype with cancerous lesions reported in histopathological studies, which tells us about the prognosis of the patients. Objective of present study was to correlate the genotype of HPV to the histopathological result evaluated in these patients at the Naval Hospital of High Specialty. Methods: A total of 316 women attended at the Naval General High Marine Hospital from 2015 to 2016 with HPV diagnosis were included, the histopathological report was correlated with the HPV genotype determined by the chain reaction of the polymerase (PCR). Statistical tests were applied for Smirnov and Kolmogorov, Chi square, OR, Anova-Kruskal Wallis. Data were processed using the SPSS software version 19 and a P <0.05 was taken as statistical significance. Results: The mean age was 36.0±10.2. The detection of cervical cancer was reported in 3.8% and stage CIN III 2.5%; the highest proportion of patients were in the CIN I stage (51.3%), while the CIN II was 9.2%, and up to 30.7% were classified as HPV infection; only 2.5% were normal. The types of HPV prevalent by PCR were those at high risk different from 16 and 18 with a rate of 34.8%, then 16 at 5.1% and 18 at 0.3%. More than half of the cases (54.4%) were negative for the serotypes analyzed. In general terms, CaCu and CIN III were observed in 15% of the type 16, 0% in type 18, 25% in other high risk and 60% in negative PCR. Conclusions: In this study, we obtained essential data that tells us that this population could be treated with low-risk HPV types associated with CaCu.